The platform economy and the commercialization of sport participation: a systematic literature review - Anisa Sholiha Mia; Andre Igoresky; Rudyanto Rudyanto (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The quick entry of digital platforms into the sphere of physical activity, fitness and leisure sports has drastically changed how participation is organised, experienced and monetised, but research still stays very much separated among sport management, marketing, information systems, and sport sociology. In order to answer these calls, we did the research by performing a systematic review of literature on platform economy as platform of commercializing sport participation. According to PRISMA 2020 rules, a structured Scopus search was carried out and 1, 418 documents were extracted and limited to years 2021, 2026. After deletion of 12 duplicates, we ended up with 1, 406 documents to be screened, of which 188 were further examined at the full-text stage and ultimately 10 were eligible studies. Eligibility was determined using predefined inclusion and exclusion criteria. Two independent reviewers conducted study screening and data extraction, with disagreements resolved through discussion (Cohen's κ = 0.88). The included studies were synthesized using the thematic synthesis framework proposed by Thomas and Harden (2008).  Commercialisation mechanisms, value co-creation, and social consequences as the main topics were explored by the means of thematic synthesis and also the combination of descriptive and bibliometric techniques. Four key messages were identified. One, commercialization is largely based on subscription and freemium models that are strengthened through engagement engineering. Second, through data-driven self-tracking and social comparison as well as parasocial relationships, platforms and their communities are made even stronger as values are co-created. Third, although these services are available online and may be free to attend, there is much to be done in that way of leisure space which can be done by surveillance, self-monitoring, and market-directed activities. The last point is that with the change in business models from ownership-centered to service-centered the whole fitness market is being changed. A new model of explaining how sport participation can be mediated through digital platforms has been developed by this review, combining the concept of platform capitalism with service-dominant logic and consumer culture theory. Commercialization studies have been expanded from just the spectator sports, besides this it also suggests some ideas or recommendations to the management, coaches or policymaking authorities and, in doing so, identifies the areas that the longitudinal, critical, and South-related research could target.